Correlation Analysis of Various Water Quality Parameters of the Tiru Reservoir, Maharashtra, India - Markad, Adinath T.; Landge, Asha T.; Kulkarni, Ajay S.; Sutar, Vijay B.; Meshre, Supriya D. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted in the department of Aquatic Environment Management, College of Fishery Science, Udgir, District Latur, Maharashtra, India during August, 2017 to January, 2019 to investigate trophic status of the Tiru reservoir. Twenty (20) water quality parameters had been collected monthly from five sampling sites of Tiru reservoir, Udgir, Latur district, Maharashtra, India. Seasonal trends were analysed and discussed in this chapter. Pearson’s correlation coefficient (r) of eighteen physico-chemical parameters from five study locations were analyzed to know the pollution causing parameters. Water quality analysis showed that Total Phosphorus concentrations was highest in the summer, when reservoir water levels were lowest. Correlation between Total phosphorus and Chl-a was highest at 0.926. Eutrophication was mainly generated by phosphorus available in the water, which increases chlorophyll-a concentration (algal blooms). A positive correlation between temperature and DO might be possible because higher summertime water temperatures boost photosynthetic activity. SDD has shown a substantial negative connection with Chl-a throughout all seasons, since an increase in phytoplankton abundance yields a decrease in water transparency. The negative correlation between SDD and turbidity is primarily caused by the high levels of productivity in the summer, and high levels of suspended organic load due to surface runoff in the monsoon season. The majority of the time throughout the research period, Tiru reservoir was found in the eutrophic state, and in some cases even hyper-eutrophic.